MODERN APPROACHES TO THE PREVENTION OF DENTAL PATHOLOGY IN EMPLOYEES OF THE CHEMICAL INDUSTRY - Ibragimova Feruza Ikromovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract.The article presents a review of the scientific literature containing data on the peculiarities of the influence of various production factors on the state of hard tissues of the teeth and oral mucosa in persons directly in contact with these factors. The pathogenesis in the development of caries and non-carious lesions, inflammatory periodontal diseases and diseases of the oral mucosa is described. The manifestations of these diseases are most often due to a pronounced sensitization of the body to harmful production factors, in the oral cavity there is a pronounced change in local immunity, homeostasis with the manifestation of dysbiosis, as a result of which the features of their clinical manifestations change.